(untitled) (Research, Society and Development, 2020)
Leprosy is a chronic infection, being considered a serious public health problem due to its magnitude and high disabling potential. In this perspective, this study aimed to analyze the epidemiological profile of leprosy patients and spatial characteristics of the disease in Aracaju, Sergipe, Brazil. This was an ecological, descriptive and analytical study of 559 leprosy patients from Aracaju, from 2011 to 2015. All information was obtained from Information System for Notifiable Injuries, Ministry of Health of Brazil. Descriptive and analytical statistical analyzes and spatial characterization methods were used. A decreasing tendency in the detection of leprosy cases during the study period was observed, with the relative frequency going from 23% (n = 129) in 2011 to 14.5% (n = 81) in 2015. The tuberculoid form was the most common (28.2%, n = 158), followed by dimorphic (24.5%, n = 137), undetermined (21.5%, n = 120) and lepromatous (20.6%; n = 115). The multibacillary operational classification also corresponded to the majority of notifications (52.4%, n = 293), with the associated factors age ≥ 16 years (OR = 2.42, 95% CI = 1.12-5.25) and male gender (OR = 2.74, 95% CI = 1.94-3.86) (p <0.05). A high risk cluster for the illness and the higher density of the mean detection incidence by the Kernel estimate was more concentrated in the central-northern portion of Aracaju. Statistical analysis allowed a better understanding of the epidemiological profile of leprosy patients and the identification of critical areas for illness and spread of the disease.